1993
DOI: 10.1136/gut.34.8.1032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age, Helicobacter pylori infection, and gastritis with atrophy on serum gastrin and gastric acid secretion in healthy men.

Abstract: Gastric acid secretion has been considered to decline with increasing age but this view is being re-evaluated as the importance of Helicobacter pylon infection emerges. This study aimed to determine the effect of age, H pylon, and gastritis with atrophy on the serum gastrin concentration, gastric secretory volumes, and acid output in healthy, asymptomatic men. Young men (mean (SD) age 22-9 (0.6) years; n=22) were compared with old men (72.9 (1-2) years; n=28) in respect of basal serum gastrin and basal, sham f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
88
3
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(106 citation statements)
references
References 23 publications
14
88
3
1
Order By: Relevance
“…As such, gastric mucosal atrophy is not the normal result of ageing, but of a pathological process. 23 This was confirmed by cohort follow-up studies, which showed that atrophic gastritis virtually only occurred in subjects with chronic gastritis. 19,24 More recently, following the recognition of the clinical importance of H. pylori, it was confirmed that this organism is a major risk factor for the development of multifocal atrophic gastritis.…”
Section: The Association With Helicobacter Pylorisupporting
confidence: 59%
“…As such, gastric mucosal atrophy is not the normal result of ageing, but of a pathological process. 23 This was confirmed by cohort follow-up studies, which showed that atrophic gastritis virtually only occurred in subjects with chronic gastritis. 19,24 More recently, following the recognition of the clinical importance of H. pylori, it was confirmed that this organism is a major risk factor for the development of multifocal atrophic gastritis.…”
Section: The Association With Helicobacter Pylorisupporting
confidence: 59%
“…This is in keeping with a previous study [21] . H pylori infection associated atrophy and intestinal metaplasia progresses with age [22,23] . Thus, older patients may be more liable to have false-negative results from the commonly biopsied sites in our practice.…”
Section: Discussionmentioning
confidence: 99%
“…For every additional illness suffered, there was a 14% increase in relative risk of being at-risk of undernutrition (NHC score Z3). Gastrointestinal disease, malabsorption syndromes, acute and chronic infections, cancer, hypermetabolism (ie, hyperthyroidism), rheumatoid arthritis and many other diseases are associated with anorexia, micronutrient deficiencies and increasing energy requirement, and may result in an impaired nutritional status (Kerstetter et al, 1992;Katelaris et al, 1993;Roubenoff, 1993;Morley, 1997;Visvanathan, 2003).…”
Section: Discussionmentioning
confidence: 99%